Faktor-Faktor Yang Memengaruhi Sustainable Entrepreneurship Pada Usaha Kecil Menengah Di Jakarta - Michael Kianto (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Entrepreneurship has both positive and negative contributions to our society. On the negative side, the degradation of  environmental  quality  caused  by  entrepreneurial  activities  requires  serious  attention.  As  such,  sustainable entrepreneurship  has  been  suggested  as  an  attempt  to  alleviate  environmental  problems. Furthermore, there are scant studies in regard to motivation and propensity in the development of sustainable entrepreneurs among SMEs practitioners.  Thus,  this  study  was  conducted  to  address  the  factors  associated  with propensity  for  sustainable entrepreneurship among owners-managers of SMEs. This sample collection through purposive sampling.  There are 100 respondents as sample of this research by using simple random sampling method. The data collection method conducted by questionnaire. Based  on  the  descriptive  analyses,  this  paper found  that  owners-managers  of  SMEs  generally  possessed  positive  or  favorable  attitude  towards  sustainability, concerned  about  social  pressures  on  sustainability,  perceived  that  sustainable  entrepreneurship  was  attractive  and perceived themselves as having sufficient ability for sustainable entrepreneurship..